Multi-Species Ethnography: On the Possibility of a Face to Face Research - Ezgi Burgan (Momentdergi, 2017)
Since 1970s human-animal studies have been investigating the relationship between humans and animals from an interdisciplinary perspective, by adopting a critical view against the dualisms such as human-animal and culture-nature. This non-anthropocentric search for a science does not mean just adding the issue of animal into the scientific research but rather gives way to questioning of the categories of “human” and “society” as things apart from “animal”. These investigations affected the ethnography itself and in 2010 S. Eben Kirksey and Stefan Helmreich defined what they termed as multi-species ethnography. It referred to a possibility of a non-anthropocentric theory and methodology in ethnography. This study explores how ethnography can relate to human-animal relations by focusing on multi-species ethnography.